Boosting Students’ Writing Proficiency through the Student Teams Achievement Division (STAD) Method: Effective Strategies and Outcomes - Puspitasari, Desi; Mayza, Elita Pretty Enggal (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2024)
This study aims to determine whether there is a significant difference in the writing skills of tenth-grade students taught using Student Teams Achievement Division (STAD) and students taught using Think Pair Share (TPS). This research employed a quantitative approach with a quasi-experimental design. This study used two classes: one class as an experimental group, while one class was used as a control group. The population taken came from class X students at SMKN 1 Ponorogo, with a total sample of 35 students. Data were collected through tests and then analyzed using the t-test formula to assess whether there was a significant difference in writing skills between students taught using the STAD technique and those taught using the TPS technique. The results of this study showed that the average value of the experimental class was 86.35, while the average value of the control class was 73.67. It indicates a difference in mean scores between the two classes. In addition, the t-test results show a significant value of 0.000, which is smaller than 0.05 (0.000 < 0.05). Therefore, it can be concluded that there is a significant difference between student writing skills using STAD and those using TPS.